2013
DOI: 10.1007/s00590-013-1337-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and management of pulseless pink/pale hand syndrome coexisting with supracondylar fractures of the humerus in children

Abstract: Elbow region fractures are the most common injuries in children. Among them, supracondylar fractures of the humerus are the most frequent. Massive displacement of the fractured bone causes severe injury to the soft tissue of that particular region. As a result, various types of injuries to the brachial artery such as entrapment, laceration, spasm of the vessel, and the presence of an intimal tear or thrombus formation are usually observed. The main goal of this study was to present our approach to children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Throughout years 1984-2002 in our Deparment only 3,6 % out of 786 fractures were operated with exploration of cubital fossa. Although hemodynamic and neurological complications are not so common, patients may present both or even brachial artery injury with multi upper limb nerve insufficiency [6,12].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Throughout years 1984-2002 in our Deparment only 3,6 % out of 786 fractures were operated with exploration of cubital fossa. Although hemodynamic and neurological complications are not so common, patients may present both or even brachial artery injury with multi upper limb nerve insufficiency [6,12].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Those said complications include signs of vascular compromise and poor blood perfusion: pain on a passive stretch of the wrist, failure to record oxygen saturation, absence of capillary refill, low hand's temperature [11]. Necessary steps in treatment of pulseless cold hand are straightforward [6] but the management of the pulseless perfused hand in association with a supracondylar humerus fracture remains controversial. Some authors have suggested the use of color-flow duplex monitoring, magnetic resonance angiography and segmental pressure monitoring as objective steps to ascertain blood flow following adequate internal fixation.…”
Section: Aimmentioning
confidence: 99%
See 2 more Smart Citations
“…While the Gartland classification does not specifically incorporate neurovascular compromise, vascular injury has been found to occur almost exclusively in extension type III or higher supracondylar humerus fractures [17], and these injuries were not considered in Gartland's classification. The brachial artery can be occluded, in spasm, entrapped, severed, or tethered by the proximal fragment of the supracondylar fracture before or after reduction.…”
Section: Limitationsmentioning
confidence: 99%